2016
DOI: 10.1016/j.jdiacomp.2015.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and all-cause mortality in patients with type 2 diabetes mellitus in the MADIABETES Cohort Study: Association with chronic kidney disease

Abstract: CKD at baseline is an independent risk factor for all-cause and cardiovascular mortality in the overall cohort, men and women, or in primary and secondary prevention of coronary heart disease. Albuminuria is an independent risk factor for all-cause and cardiovascular mortality only in primary prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 45 publications
1
32
0
Order By: Relevance
“…8 The slower decrease in eGFR associated with dulaglutide compared with insulin glargine is especially important given the increased risk of cardiovascular disease and premature mortality associated with comorbid T2D and CKD. 27,28 The LEADER study also found that the slope of the eGFR decrease was attenuated when patients with eGFR <60 and 30 mL/min/1.73 m 2 took liraglutide compared with placebo. 9 Real-world outcomes research is relatively limited regarding renal outcomes with GLP-1 RA treatment, and such studies mostly have included a limited number of participants.…”
Section: T a G G E D H 1 Discussiont A G G E D E N Dmentioning
confidence: 97%
“…8 The slower decrease in eGFR associated with dulaglutide compared with insulin glargine is especially important given the increased risk of cardiovascular disease and premature mortality associated with comorbid T2D and CKD. 27,28 The LEADER study also found that the slope of the eGFR decrease was attenuated when patients with eGFR <60 and 30 mL/min/1.73 m 2 took liraglutide compared with placebo. 9 Real-world outcomes research is relatively limited regarding renal outcomes with GLP-1 RA treatment, and such studies mostly have included a limited number of participants.…”
Section: T a G G E D H 1 Discussiont A G G E D E N Dmentioning
confidence: 97%
“…The MADIABETES Cohort Study showed that the coexistence of CKD in patients with type 2 diabetes mellitus was an independent risk factor for all-cause and CV mortality [11].…”
Section: Diabetes and Hypertensionmentioning
confidence: 99%
“…According to Matsushita et al [14], albuminuria is independently associated with heart mass, systolic and diastolic functions of left ventricle. The level of albumin is currently considered as a potential predictor of mortality and hospitalization risk [15].…”
Section: Diabetes and Hypertensionmentioning
confidence: 99%
“…The Madrid Diabetes Study, which is a prospective cohort study of 3443 type-2 diabetic outpatients, showed that the unadjusted hazard ratio for all-cause mortality in diabetic patients with eGFR < 60 mL/min/1.73 m 2 was approximately 3 after five years of follow-up. Patients with chronic kidney disease at baseline had an increased risk of cardiovascular mortality [24]. …”
Section: The Impact Of Chronic Hyperglycemia On Diabetic Complicationmentioning
confidence: 99%